Global Attractivity of a Periodic Delayed N-Species Model of Facultative Mutualism - Ahmadjan Muhammadhaji; Zhidong Teng (Discrete Dynamics in Nature and Society)
Two classes of periodic N-species Lotka-Volterra facultative mutualism systems with distributed delays are discussed. Based on the continuation theorem of the coincidence degree theory developed by Gaines and Mawhin and the Lyapunov function method, some new sufficient conditions on the existence and global attractivity of positive periodic solutions are established.